Addressing viral risk in drinking water: evaluating the impact of treatment processes in drinking water treatment - Barry, Hannah Louise (Cranfield University, 2023)
Drinking water treatment is designed to improve water quality, including the removal of potential contaminants like viruses. Pilot-scale studies can provide valuable insights into the effectiveness of full-scale treatment processes in managing viral risks. While traditional water treatment processes are effective in removing many contaminants, the specific removal of viruses remains a significant concern. The World Health Organization (WHO) recommends a 2-log reduction of enteric viruses from source to tap water. However, the effectiveness of different treatment processes in achieving this target, especially under varying conditions, requires further investigation. This study demonstrated that optimized coagulation, followed by subsequent treatment processes, can effectively remove Φ-X174 from water, even at high initial concentrations. The results suggest that conventional drinking water treatment methods can effectively manage the risk of viral contamination, aligning with the WHO's recommended log removal target. This study optimised coagulation and conducted challenge trials using a near- real scale drinking water treatment rig to evaluate the effectiveness of individual treatment processes and log reduction of Φ-x 174. At a final concentration of 1010 plaque-forming units of Φ-X 174 the somatic coliphage was not detected in the final water. At a final concentration of 1014 plaque-forming units of Φ-X 174, coliphage was detected with no coagulant dose but was removed to below the detection limit for both optimal (10 mg-Fe3+ /L) and sub-optimal (2 mg-Fe3+ /L) coagulation conditions.
Jarvis, Peter - Associate Supervisor Singh, Suniti - Associate Supervisor
Keywords: Virus removal; coagulation; pilot-scale; optimal coagulation; sub-optimal coagulation; Phi-X 174